Selling Hospice. Issue 4 (2014) - Halabi, Sam
Abstract : Hospice care in the United States has undergone a remarkable transformation since it assumed its modern form in the late 1960s. It began as a movement driven by small organizations staffed with many volunteer providers focusing on comprehensive spiritual, palliative, and mental health services for a relatively small number of terminally ill patients, typically suffering from cancer. The idea behind hospice during its early days was that a terminally patient and his or her family made a decision to focus on easing a patient's pain and anxiety, making him or her more comfortable, rather than pursuing additional curative treatment. Because these objectives required a wide range of professional and non-professional skills, hospice care involved not only physicians and nurses, but clergy, social workers, volunteer caretakers, homemakers, and, of course, family members. The process of decision-making by the patient and his or her family was never uniform and never systematically studied.